Method for recycling polyester resin and method for manufacturing synthetic resin container

The solid phase polymerization method under reduced pressure effectively addresses quality deterioration and impurity issues in recycled polyester resin, enhancing recyclability and productivity by restoring intrinsic viscosity and removing contaminants.

JP7615646B2Active Publication Date: 2025-01-17TOYO SEIKAN KAISHA LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020203010
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-07
Publication Date
2025-01-17
Estimated Expiration
2040-12-07

AI Technical Summary

Technical Problem

Mechanical recycling of polyester resin molded products, such as PET bottles, faces issues with quality deterioration due to thermal history, leading to defects in recycled products and contamination of manufacturing equipment, along with decreased productivity from impurities like acetaldehyde, bishydroxyethyl terephthalate, monohydroxyethyl terephthalate, and cyclic compounds.

Method used

A method involving solid phase polymerization under reduced pressure conditions to regenerate recycled polyester resin, including primary and secondary solid phase polymerization steps, followed by granulation into pellets, to restore intrinsic viscosity and remove impurities.

Benefits of technology

The method effectively regenerates polyester resin for reuse, reducing impurities and improving recyclability, preventing defects and contamination, and enhancing productivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007615646000001
    Figure 0007615646000001
Patent Text Reader

Abstract

To solve a problem occurring when recycling the collected polyester resin molded articles as a recycled material by mechanical recycling.SOLUTION: A regeneration method for used polyester resin molded articles includes: a primary solid phase polymerization process of heating resin flakes prepared by pulverizing the collected polyester resin molded article into a flaky shape in a temperature range of more than a glass transition point but less than the melting point thereof under a reduced pressure condition of 50 mbar or less; a granulation process of plasticizing, melting and kneading the resin flake after the above polymerization process to granulate into a pellet form; and a secondary solid phase polymerization process of heating the resin pellet prepared by the granulation process at a temperature in the range of 180 to 230°C under the reduced pressure condition of 100 mbar or less. The polyester resin is regenerated through those processes.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for recycling polyester resins and a method for producing synthetic resin containers. [Background technology]

[0002] Conventionally, synthetic resin containers, which are made by producing a bottomed cylindrical preform using a polyester resin such as polyethylene terephthalate and then molding this preform into a bottle shape by biaxial stretch blow molding or the like, are used in a wide range of fields as containers for various beverages, seasonings, etc. This type of container is generally known as a PET bottle, and in recent years, in response to social demand, a recycling technology called "bottle-to-bottle" has been considered, in which used PET bottles are collected and reused as recycled material to manufacture PET bottles.

[0003] For example, Patent Document 1 discloses a technology for mechanical recycling in which used plastic bottles are crushed and washed to produce resin flakes, contaminants contained in the resin flakes are decontaminated by volatilizing them through heating under a vacuum, and the flakes are then supplied in a molten state through a filter to an injection molding machine to injection mold preforms. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2019-514728 Summary of the Invention [Problem to be solved by the invention]

[0005] However, when polyester resin molded products such as used PET bottles are collected and reused as recycled materials by mechanical recycling to manufacture recycled products from the collected products, there is a problem that the decrease in intrinsic viscosity due to the deterioration of the resin quality caused by the heat history during the manufacture of the collected products causes defects in the manufacturing process of the recycled products. Furthermore, if a large amount of acetaldehyde (AA) generated by thermal decomposition of polyester resin, oligomers such as bishydroxyethyl terephthalate (BHET), monohydroxyethyl terephthalate (MHET), and cyclic trimer (CT) generated by depolymerization of polyester resin, and limonene derived from the contents remain in the recycled materials, they not only affect the quality of the recycled products manufactured, but also cause problems such as soiling the manufacturing equipment, thereby reducing productivity.

[0006] Therefore, the present inventors have conducted extensive research to solve the above-mentioned problems that arise when recovering polyester resin molded articles as recycled materials by mechanical recycling, and as a result have completed the present invention. [Means for solving the problem]

[0007] The method for regenerating polyester resin according to the present invention is a method for regenerating polyester resin by crushing recovered polyester resin molded products into flakes, and then subjecting the resin flakes to a temperature range of not less than the glass transition point and not more than the melting point under reduced pressure conditions of not more than 50 mbar. The temperature at which solid-state polymerization reaction proceeds Heating with The resin flakes are then subjected to a solid-phase polymerization reaction without being melted, while still in the form of flakes. a granulation step in which the resin flakes that have been subjected to the primary solid-state polymerization step are plasticized, melt-kneaded, and granulated into pellets; and 20 Under reduced pressure below mbar, in the range of 180 to 230°C The temperature at which solid-state polymerization reaction proceeds Heating with Then, the solid-state polymerization reaction is carried out again. and a secondary solid-state polymerization step.

[0008] The method for manufacturing a synthetic resin container according to the present invention involves plasticizing the pellet-shaped recycled polyester resin recycled by the above-mentioned method, melt-kneading it, and producing a bottomed cylindrical preform by injection molding or compression molding, and then blow molding the preform. Effect of the Invention

[0009] According to the present invention, when the recovered polyester resin molded articles are reused as recycled materials by mechanical recycling, the polyester resin is well regenerated, so that the articles can be suitably reused as recycled materials. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Preferred embodiments of the present invention will now be described.

[0011] In this embodiment, the polyester-based resin of degraded quality that forms the collected polyester-based resin molded products is regenerated so that the collected polyester-based resin molded products can be suitably reused as recycled materials by mechanical recycling. The "collected polyester-based resin molded products" can include polyester-based resin molded products such as used PET bottles that have been collected separately as resource waste, as well as scrap materials generated during the manufacturing process of polyester-based resin molded products.

[0012] Examples of polyester resins that can be recycled include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polyethylene furanoate, and copolymers thereof.

[0013] In this embodiment, the recovered polyester resin molded products are first crushed into flakes and washed by any washing means such as alkaline washing or hot water washing to remove dirt such as residues of contents remaining on the surface of the crushed resin flakes and foreign matter mixed in. The washed resin flakes are then dried as necessary and then charged into a solid-state polymerization tank (hereinafter referred to as a "primary solid-state polymerization tank") prepared for the resin flakes, and heated in a range from the glass transition point to the melting temperature under reduced pressure conditions of 50 mbar or less, preferably 20 mbar or less, to proceed with a solid-state polymerization reaction in the flake form without melting the resin flakes (primary solid-state polymerization step).

[0014] Next, the resin flakes that have been subjected to the primary solid-phase polymerization step are plasticized, melt-kneaded, and granulated into pellets to produce resin pellets (granulation step).

[0015] To carry out the granulation step, for example, a granulation device can be used, which is equipped with a heating cylinder with a plasticizing screw disposed therein and a granulation die attached to the tip of the heating cylinder, and is configured to cut the resin into pellets after plasticization and melt-kneading in the heating cylinder and extruded in a strand shape from the granulation die. In such a granulation device, a filter for removing foreign matter can be interposed between the granulation die and the heating cylinder. From the viewpoint of efficient processing, it is preferable to connect these devices so that the resin flakes that have undergone the primary solid-state polymerization step are directly fed from the primary solid-state polymerization tank into the granulation device, thereby allowing the primary solid-state polymerization step and the granulation step to be carried out continuously.

[0016] Thereafter, in this embodiment, the resin pellets produced in the granulation process are charged into a solid-state polymerization tank (hereinafter referred to as a "secondary solid-state polymerization tank") prepared for the resin pellets, and heated to a temperature in the range of 180 to 230°C, preferably 190 to 210°C, under reduced pressure conditions of 100 mbar or less, preferably 20 mbar or less, to allow the solid-state polymerization reaction to proceed again (secondary solid-state polymerization process).

[0017] When carrying out the secondary solid-state polymerization step, it is preferable to preheat the resin pellets to a temperature of, for example, 140 to 180°C at a temperature at which the solid-state polymerization reaction does not proceed, and increase the crystallinity of the surfaces of the resin pellets that have been amorphized in the granulation step, thereby suppressing blocking between the resin pellets in the secondary solid-state polymerization tank.

[0018] The solid-state polymerization reaction causes the end groups of the polyester resin, whose degree of polymerization has been reduced by the cutting of molecular chains due to deterioration, to re-condense, and as the degree of polymerization is restored, the intrinsic viscosity (IV) corresponding to the molecular weight can be restored. In this embodiment, the solid-state polymerization reaction is carried out in the state of resin flakes to carry out a first solid-state polymerization process, and then the resin flakes that have been through the first solid-state polymerization process are plasticized, melt-kneaded, and pelletized into pellets, and then the solid-state polymerization reaction is carried out again in the state of resin pellets to carry out a second solid-state polymerization process, thereby efficiently restoring the intrinsic viscosity of the polyester resin while suppressing thermal decomposition and depolymerization of the polyester resin.

[0019] In addition, by carrying out the solid-phase polymerization reaction under reduced pressure, it is possible to remove low molecular weight impurities such as acetaldehyde generated by thermal decomposition of the polyester resin, oligomers such as BHET, MHET, and CT generated by depolymerization of the polyester resin, monomer-derived components such as DEG derived from the monomer before polymerization, limonene derived from the contents, and moisture sorbed in the resin by volatilization or evaporation under reduced pressure. In this embodiment, by carrying out the first solid-phase polymerization process in the state of resin flakes before granulating into resin pellets, it is possible to remove these impurities remaining on the surface of the resin flakes while suppressing the incorporation of impurities into the resin pellets. In addition, by efficiently removing impurities that have seeped out onto the surface of the resin pellets during the process of plasticizing the resin flakes and granulating them into pellets in the second solid-phase polymerization process, it is possible to more effectively reduce the amount of impurities remaining in the resin pellets finally obtained. When removing impurities by carrying out the solid-state polymerization reaction under reduced pressure conditions, it is preferable to use an inert gas such as N2 gas as a carrier gas and continuously flow the gas into and out of a solid-state polymerization reactor at a predetermined flow rate while maintaining the reduced pressure state.

[0020] According to the present embodiment as described above, when the collected polyester resin molded product is reused as a recycled material by mechanical recycling, the polyester resin is well regenerated, so that it can be suitably reused as a recycled material. In particular, in this embodiment, the resin pellets made of the recycled polyester resin are plasticized, melt-kneaded, and injection-molded or compression-molded to prepare a bottomed cylindrical preform, and then blow-molded the preform, so that it is suitable as a recycled material for manufacturing synthetic resin containers such as PET bottles. Since the first melting point peak of the resin pellets is shifted from the low temperature side to the high temperature side due to thermal crystallization in the secondary solid-phase polymerization process, there is no problem such as blocking during drying treatment before preform molding. EXAMPLES

[0021] The present invention will now be described in more detail with reference to specific examples.

[0022] [Example 1] The collected used PET bottles were crushed into flakes, and washed resin flakes were prepared. The prepared resin flakes were put into a first solid-state polymerization tank and heated to about 210°C under reduced pressure conditions of 20 mbar or less, and the solid-state polymerization reaction proceeded while the resin flakes were in the flake form without melting them. The resin flakes were then plasticized and melt-kneaded to pelletize the resin flakes that had undergone the first solid-state polymerization step, so that the resin flakes were placed in the first solid-state polymerization tank for 60 to 90 minutes before being placed in a granulator. The resin pellets were then placed in a second solid-state polymerization tank and heated to 200°C under reduced pressure conditions of 10 mbar or less, and the solid-state polymerization reaction proceeded again. The resin pellets were then placed in the second solid-state polymerization tank for 6 hours, and discharged after the second solid-state polymerization step. In addition, when performing the secondary solid-state polymerization process, the inflow and exhaust of N2 gas into the secondary solid-state polymerization tank was controlled at 3 m 3 The experiment was carried out continuously at a flow rate of 100 / L.

[0023] The intrinsic viscosity (IV), crystallinity, melting point (Tm), and residual amounts of acetaldehyde (AA), BHET, MHET, and CT were measured for the resin pellets after the secondary solid-state polymerization process. The results are shown in Table 1. The intrinsic viscosity (IV), the degree of crystallinity, the melting point (Tm), and the remaining amounts of acetaldehyde (AA), BHET, MHET, and CT were measured as follows.

[0024] <Intrinsic viscosity> The resin pellets were vacuum dried at 150°C for 1 hour and weighed out at 0.2 g. A mixed solvent of 1,1,2,2-tetrachloroethane and phenol (weight ratio 1 / 1) was added to the pellets to adjust the concentration to 1.00 g / dL, and the pellets were stirred at 120°C for 20 minutes to completely dissolve the pellets. The dissolved solution was cooled to room temperature, and the relative viscosity was measured using a relative viscometer (Viscotek, Y501) adjusted to 30°C, to determine the intrinsic viscosity.

[0025] <Crystallization degree> The crystallinity was calculated by the density method using the following formula: Crystallinity χ c={[ρc×(ρ - ρa)] / [ρ×(ρc - ρa)]} ρ: Measured density (g / cm 3 ) ρa: Amorphous density (1.335 g / cm 3 ) ρc: Crystalline density (1.455 g / cm 3 ) Note that the density measurement was performed using a calcium nitrate solution-based density gradient tube (Shibayama Scientific Instruments Co., Ltd.) under the condition of 23°C.

[0026] <Melting point> Using 8 mg of resin pellets as the sample, DSC measurement was performed using a differential scanning calorimeter (DSC8500 manufactured by PERKIN ELMAR). The sample temperature was (1) Held at 40°C for 3 minutes (2) Heated from 40°C to 300°C at a rate of 10°C / min Scanned in this order, and the melting point peak in (2) was taken as the melting point. The melting point peak on the low temperature side was taken as the first melting point peak, and the melting point peak on the high temperature side was taken as the second melting point peak.

[0027] <Residual amount of acetaldehyde> Weighed 1.0 g of the pulverized sample of resin pellets pulverized by a cryogenic pulverizer into a glass bottle, added 5.0 mL of pure water, and sealed it. This suspension was heated in an oven maintained at 120°C for 60 minutes, and then cooled in ice water. 1.0 mL of the supernatant of the suspension was collected, 0.2 mL of a 2,4-dinitrophenylhydrazine·phosphoric acid solution with a concentration of 0.1% was added thereto, and the mixture left standing for 30 minutes was measured by high performance liquid chromatography. At the same time, the standard solution was also measured, and the acetaldehyde content in the resin pellets was calculated based on the obtained calibration curve.

[0028] <Residual amounts of BHET, MHET, and CT> 0.2 g of resin pellets were weighed out, and 1 mL of a mixed solvent of hexafluoroisopropanol and chloroform (weight ratio 1 / 1) was added to completely dissolve it. 4 mL of chloroform was added to the solution, and then 5 mL of acetonitrile was gradually added and left for 3 hours to precipitate the PET polymer. 1 mL of this suspension was taken and filtered through a membrane filter with a pore size of 0.45 μm, and the filtrate was measured by high performance liquid chromatography. At the same time, the standard solution was also measured, and the contents of MHET, BHET, and CT in the pellets were calculated based on the obtained calibration curve.

[0029] [Table 1]

[0030] [Example 2] The same operation as in Example 1 was carried out except that the heating temperature in the secondary solid-state polymerization step was 195° C., and the intrinsic viscosity (IV), crystallinity, melting point (Tm), and residual amounts of acetaldehyde (AA), BHET, MHET, and CT were measured for the resin pellets after the secondary solid-state polymerization step. The results are shown in Table 1.

[0031] [Comparative Example 1] The collected used PET bottles were crushed into flakes, and the washed resin flakes were prepared. They were dried by heating at 160°C for about 100 minutes without proceeding with the solid-state polymerization reaction, and then fed into a granulator to be granulated into pellets. The intrinsic viscosity (IV), crystallinity, melting point (Tm), and residual amounts of acetaldehyde (AA), BHET, MHET, and CT were measured for the obtained resin pellets. The results are shown in Table 1.

[0032] [Comparative Example 2] The resin pellets obtained in Comparative Example 1 were charged into a solid-state polymerization tank, and the solid-state polymerization reaction was carried out by heating to 200°C under reduced pressure of 10 mbar or less in the same manner as in Example 1, except that the residence time of the resin pellets was set to 6 hours. The intrinsic viscosity (IV), crystallinity, melting point (Tm), and residual amounts of acetaldehyde (AA), BHET, MHET, and CT were measured for the resin pellets after solid-state polymerization. The results are shown in Table 1. The improvement in crystallinity compared to Examples 1 and 2 is believed to be due to the longer residence time of the resin pellets. However, other than that, the results were inferior to those of Examples 1 and 2.

[0033] [Comparative Example 3] The collected used PET bottles were crushed into flakes, and washed resin flakes were prepared. The prepared resin flakes were put into a solid-state polymerization tank and heated to about 190°C under reduced pressure of 10 mbar or less, so that the solid-state polymerization reaction proceeded without melting the resin flakes in the flake form. The resin flakes were then pelletized by being put into a pelletizer after remaining in the solid-state polymerization tank for about 90 minutes. The intrinsic viscosity (IV), crystallinity, melting point (Tm), and residual amounts of acetaldehyde (AA), BHET, MHET, and CT were measured for the obtained resin pellets. The results are shown in Table 1. The resin pellets obtained in this comparative example had a first melting point peak in the vicinity of 160 to 190° C., and problems such as blocking occurred during the drying treatment before preform molding.

[0034] [Comparative Example 4] The collected used PET bottles were crushed into flakes, and washed resin flakes were prepared. The prepared resin flakes were put into a solid-state polymerization tank and heated to about 190°C under reduced pressure of 10 mbar or less, so that the solid-state polymerization reaction proceeded without melting the resin flakes in the flake form. The resin flakes were pelletized by being put into a pelletizer after staying in the solid-state polymerization tank for about 120 minutes. The intrinsic viscosity (IV), crystallinity, melting point (Tm), and residual amounts of acetaldehyde (AA), BHET, MHET, and CT were measured for the obtained resin pellets. The results are shown in Table 1.

[0035] [Comparative Example 5] The resin pellets obtained in Comparative Example 4 were heat-treated at 160°C for 6 hours under normal pressure. The intrinsic viscosity (IV), crystallinity, melting point (Tm), and residual amounts of acetaldehyde (AA), BHET, MHET, and CT were measured for the resin pellets after the heat treatment. The results are shown in Table 1. In comparison with Comparative Example 4, no significant changes were observed in the intrinsic viscosity and crystallinity when the heat treatment was performed at 160° C. as in this Comparative Example.

[0036] [Comparative Example 6] In the secondary solid-state polymerization step, the pressure in the secondary solid-state polymerization tank was adjusted to 100 to 200 mbar, the heating temperature was set to 197°C, and the flow rate of N2 gas was set to 200 m 3 The same procedure as in Example 1 was carried out except that the concentration was changed to 1 / L, and the intrinsic viscosity (IV), crystallinity, melting point (Tm), and residual amounts of acetaldehyde (AA), BHET, MHET, and CT were measured for the resin pellets after the secondary solid-state polymerization step. The results are shown in Table 1. Although the intrinsic viscosity was improved to the same extent as in Examples 1 and 2, the results were otherwise inferior to those of Examples 1 and 2.

[0037] The recycled polyester resin according to the present invention is a recycled polyester resin recycled by the above-mentioned recycling method, and is well recycled from recovered polyester resin molded products so that the intrinsic viscosity is 0.78 to 0.95 dl / g, the crystallinity is 40 to 60%, the first melting point peak is 200 to 245°C, the residual amount of acetaldehyde is 0.1 to 2.0 ppm, the residual amount of bishydroxyethyl terephthalate is 5 to 18 ppm, the residual amount of monohydroxyethyl terephthalate is 5 to 18 ppm, and the residual amount of cyclic trimer is 4,000 to 7,000 ppm.

[0038] Although the present invention has been described above by showing preferred embodiments, it goes without saying that the present invention is not limited to the above-described embodiments, and various modifications can be made within the scope of the present invention.

Claims

1. a primary solid-state polymerization step in which the resin flakes obtained by crushing the recovered polyester resin molded articles into flakes are heated under reduced pressure conditions of 50 mbar or less at a temperature at which a solid-state polymerization reaction proceeds within a range of not less than the glass transition point and not more than the melting temperature, thereby proceeding with a solid-state polymerization reaction while the resin flakes remain in the flake-like form without melting the resin flakes; a granulation step in which the resin flakes that have undergone the primary solid-phase polymerization step are plasticized, melt-kneaded, and granulated into pellets; a secondary solid-state polymerization step in which the resin pellets produced in the granulation step are heated under reduced pressure conditions of 20 mbar or less at a temperature within a range of 180 to 230° C. at which a solid-state polymerization reaction proceeds, thereby causing the solid-state polymerization reaction to proceed again; A method for regenerating a polyester resin, comprising:

2. A method for producing a synthetic resin container, comprising the steps of: plasticizing pellet-shaped recycled polyester resin recycled by the method for recycling polyester resin described in claim 1; melt-kneading the pellet-shaped recycled polyester resin; and producing a bottomed cylindrical preform by injection molding or compression molding. The method comprises blow molding the preform.

3. A recycled polyethylene terephthalate resin regenerated by the method for regenerating a polyester resin according to claim 1, A recycled polyethylene terephthalate resin having an intrinsic viscosity of 0.78 to 0.95 dl / g, a degree of crystallinity of 40 to 60%, a first melting point peak of 200 to 245°C, a residual amount of acetaldehyde of 0.1 to 2.0 ppm, a residual amount of bishydroxyethyl terephthalate of 5 to 18 ppm, a residual amount of monohydroxyethyl terephthalate of 5 to 18 ppm, and a residual amount of cyclic trimer of 4,000 to 7,000 ppm.

Citation Information

Patent Citations

  • Resin bottle with label and method for regenerating resin bottle

    JP2000000873A

  • Resin-made bottle with label stuck thereon and its recycling method

    JP2001058620A

  • Method for recycling pet bottle

    JP2002011719A

  • Polyester resin for compression molding, method for producing preform and preform

    JP2006052307A

  • Multilayer container and method for producing recycled polyester

    JP2018043773A